2023
DOI: 10.1101/2023.08.10.552835
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Probing for Intentions: The Early Readiness Potential Does Not Reflect Awareness of Motor Preparation

Jake Gavenas,
Aaron Schurger,
Uri Maoz

Abstract: Voluntary actions are typically preceded by the Readiness Potential (RP), a negative midfrontal EEG deflection that begins ~2 seconds before movement. What cognitive and neural process the RP reflects and how it relates to conscious intention remain unclear due to conflicting findings. We investigated the neural basis and cognitive significance of the RP in a novel probe-based paradigm. Contrary to prior reports, we found that pre-probe RP buildups were not related to reported awareness of motor preparation. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
(203 reference statements)
0
0
1
Order By: Relevance
“…This finding offers support for the proposal that successful putts are associated with reduced response programming demands ( Wright et al, 2012 ) requiring less energy ( Di Russo et al, 2005 ). These findings may seem contradictory to the beta findings presented above, but recent research has suggested that beta and RP could reflect different phenomena within the movement preparation processes ( Gavenas et al, 2023 ; Parés-Pujolràs et al, 2023 ). We recommend that future research explores how beta desynchronization in the motor cortex relates to the RP.…”
Section: Discussioncontrasting
confidence: 86%
“…This finding offers support for the proposal that successful putts are associated with reduced response programming demands ( Wright et al, 2012 ) requiring less energy ( Di Russo et al, 2005 ). These findings may seem contradictory to the beta findings presented above, but recent research has suggested that beta and RP could reflect different phenomena within the movement preparation processes ( Gavenas et al, 2023 ; Parés-Pujolràs et al, 2023 ). We recommend that future research explores how beta desynchronization in the motor cortex relates to the RP.…”
Section: Discussioncontrasting
confidence: 86%